Social and psychological bases of ideology and system justification - Jost, John T.; Kay, Aaron C.; Thorisdottir, Hulda (Series in political psychology., 2009)
This new volume on 'Social and Psychological Bases of Ideology and System Justification' brings together several of the most prominent social and political psychologists who are responsible for the resurgence of interest in the study of ideology, broadly defined.